Religious Music and Secular Music: A Calvinist Perspective, Re-formed - Brown, Frank Burch (Theology today, 2006)
Although Calvin's theology of music runs counter to the tenor of our times, it can be reformed so as to alert us to both assets and risks of music in Christian worship and life. In particular, Calvin can help reintroduce critical discernment in a context in which churches appear eager to absorb virtually every style of secular music (the reverse of what Calvin desired). More positively, he can encourage us to find and create music that not only touches the heart but lends itself to the high calling of lifting hearts into “the presence of God and the angels.”